Kinerja Majelis Pengawas Daerah Notaris Dalam Pengelolaan Protokol Notaris Di Kota Jakarta Barat - Ningsih, Retno Wahyu; Jeddawi , Murtir; Wargadinata , Ella L. (UIR Press, 2025)
The authentic deed is a perfect instrument of evidence. A notary is a public official, authorized to make an authentic deed. One of the notary obligations is to compose the deeds in the form of minute and preserve them. The obligation to save the minute of the deed is to keep the authenticity of the deed by storing documents in its original form. In the event that a notary retires or dies, it is kept in place through the protocols of the notary. The notary protocol is a collection of documents which are state records that should be treated and properly stored by a notary who holds the protocol. As state records, authentic deeds are required by society as instruments of evidence to ensure legal certainty. Under the terms of the regulatory regulations, the protocols of the notary to be referred to the notary regency of notary (MPDN) by the notary. For the notary dead, the protocols of the notary must be handed over to MPDN by the heir of the notary who has passed away. So also the protocol of other notary notaries at the time of their being 25 (twenty-five) years of age or older also had to be submitted by notary recipients of notary protocols to the MPDN to then the MPDN appointed an active notary as the recipient of the notary protocols. The research aimed at knowing the extent of west Jakarta's performance in managing notary protocols, the obstacles faced and the efforts to overcome those barriers. This research method employs descriptive qualitative research methods. Research techniques use data analysis with data studies based on documents about MPDN, notary and notary protocols and the results of interviews with sources on the subject of research. Research suggests that the firmness of the MPDN is greatly needed in designating another notary as a notary holder of a notary protocols of a retired notary, passed away as well as other notary protocols of a notary of any other when it is 25 (twenty-five) years of age or older. Notary protocols that are not handed over to other notaries as protocol holders result in loss to society.